2008
DOI: 10.1093/rpd/ncn192
|View full text |Cite
|
Sign up to set email alerts
|

Variation of soil radon concentrations in southern Ontario

Abstract: Radon has been identified as the second leading cause of lung cancer after tobacco smoking. Information on indoor radon concentrations is required to assess the lung cancer burden due to radon exposure. However, radon data in highly populated southern Ontario are very limited. Since radon in soil is believed to be the main source of radon in homes, measurements of soil gas radon concentrations can be used to estimate variations in radon potential of indoor environments. This study reports a transect survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As a contribution to the NRP the first in-situ survey of terrestrial radionuclides in soil was conducted in the summer of 2007 at 32 sites spaced at mean intervals of 40 km along a transect spanning southern Ontario between Ottawa and Sarnia [8]. Survey sites were located either along the outer margins of road allowances, >10 m from roads, or in farmer's fields and wooded areas where permitted by property owners.…”
Section: Measurement Activities Of Terrestrial Gamma Raysmentioning
confidence: 99%
See 1 more Smart Citation
“…As a contribution to the NRP the first in-situ survey of terrestrial radionuclides in soil was conducted in the summer of 2007 at 32 sites spaced at mean intervals of 40 km along a transect spanning southern Ontario between Ottawa and Sarnia [8]. Survey sites were located either along the outer margins of road allowances, >10 m from roads, or in farmer's fields and wooded areas where permitted by property owners.…”
Section: Measurement Activities Of Terrestrial Gamma Raysmentioning
confidence: 99%
“…The ground surveys were carried out over 4 years from 2007 to 2010. Survey results of GGRS, SGR, and soil permeability were reported in previous publications [8][9][10][11][12][13][14]. Results of in-situ measurements of natural radioactivity in soil using GGRS are summarised here.…”
Section: Introductionmentioning
confidence: 99%
“…This multi-step approach could potentially optimize the use of resources and is already implemented in the recent activities. A preliminary study of natural background variation in soil radon levels (Chen et al 2008d) was carried out in summer 2007 at mean intervals of 40 km along a transect spanning southern Ontario between Ottawa and Sarnia where virtually no data are available to characterize variations in indoor radon concentrations except the city of Toronto. The results indicated that radon risk could be high in some areas of southern Ontario, and helped prioritizing the airborne gamma survey in the following year in the heavily populated southern Ontario.…”
Section: A Multi-tier Approachmentioning
confidence: 99%
“…Previous SRP work has been completed for parts of southern Ontario (Chen et al 2008) when the Ottawa-Sarnia transect was analyzed for the radon potential. Natural soil gas radon variability and background concentrations were determined at 32 sites between Ottawa and Sarnia.…”
Section: Introductionmentioning
confidence: 99%